2007
DOI: 10.1021/jo070144x
|View full text |Cite
|
Sign up to set email alerts
|

Explorations on the Asymmetric Total Synthesis of Isoschizogamine

Abstract: Two approaches to the synthesis of isoschizogamine were reported. Both routes utilized an efficient aza-Claisen rearrangement to establish the absolute stereochemistry of the all-carbon quaternary center in the natural product. In the first approach, a highly diastereoselective (10:1) hetero-Diels-Alder reaction was utilized to reach a densely functionalized tetrahydroquinoline derivative as an advanced intermediate to the targeted alkaloid. An acylamidine intermediate was prepared and studied in the intramole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…In this context, N ‐acyl vinylaziridines 25 has been successfully converted into the corresponding 7‐membered lactams ( 27 ) through ACR‐induced ring expansion (Scheme A) . This strategy was used for the synthesis of an isoschizozygane alkaloid (Scheme B) . However, the original conditions reported by Lindström and Somfai (LHMDS, THF, −78 to 0 °C) did not promote the expected rearrangement of substrate 28 ; instead, the desired 7‐membered lactam ( 29 ) was produced by heating (80 °C) in toluene after deprotonation (LHMDS, toluene, −78 °C, 30 min).…”
Section: Acr‐induced Ring‐expansion Strategies For the Synthesis Of Mmentioning
confidence: 99%
“…In this context, N ‐acyl vinylaziridines 25 has been successfully converted into the corresponding 7‐membered lactams ( 27 ) through ACR‐induced ring expansion (Scheme A) . This strategy was used for the synthesis of an isoschizozygane alkaloid (Scheme B) . However, the original conditions reported by Lindström and Somfai (LHMDS, THF, −78 to 0 °C) did not promote the expected rearrangement of substrate 28 ; instead, the desired 7‐membered lactam ( 29 ) was produced by heating (80 °C) in toluene after deprotonation (LHMDS, toluene, −78 °C, 30 min).…”
Section: Acr‐induced Ring‐expansion Strategies For the Synthesis Of Mmentioning
confidence: 99%
“…The high optical purity (97% ee) shows that the stereochemistry of the aziridine was transferred to the quaternary center with high fidelity (Scheme 13). 29…”
Section: Scheme 12mentioning
confidence: 99%
“…To date, one racemic total synthesis by Heathcock and two synthetic studies have been reported. [54][55][56][57][58] Chart 4 depicts our synthesis of isoschizogamine. Oxidation of exo-norborneol (48) and a subsequent reaction with trisyl hydrazide afforded hydrazone 49.…”
Section: Synthesis Of Isoschizogaminementioning
confidence: 99%